Road rage : [compact disc, unabridged] : two novellas. - Matheson, Richard, 1926-2013; Hill, Joe; Hill, Joe; Lang, Stephen, 1952- (Harper Audio, 2009)
Duel: A businessman finds himself pitted against an anonymous truck driver in a deadly game of cat and mouse on a Californian highway.